2022
DOI: 10.1038/s41531-022-00423-7
|View full text |Cite
|
Sign up to set email alerts
|

Protein aggregation and calcium dysregulation are hallmarks of familial Parkinson’s disease in midbrain dopaminergic neurons

Abstract: Mutations in the SNCA gene cause autosomal dominant Parkinson’s disease (PD), with loss of dopaminergic neurons in the substantia nigra, and aggregation of α-synuclein. The sequence of molecular events that proceed from an SNCA mutation during development, to end-stage pathology is unknown. Utilising human-induced pluripotent stem cells (hiPSCs), we resolved the temporal sequence of SNCA-induced pathophysiological events in order to discover early, and likely causative, events. Our small molecule-based protoco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 75 publications
0
28
0
Order By: Relevance
“…Oligomers produced during secondary surface nucleation induce the permeabilization of cell membranes through to their lipophilic properties. Associated with these events, higher basal levels of cytosolic Ca 2+ , increased Ca 2+ influx upon stimulation, and delayed recovery of Ca 2+ levels in neurons are then observed since the early phases, leading to multiple Ca 2+ homeostasis alterations that persist with disease progression [ 18 ].…”
Section: Alpha-synuclein Structure and Physiological Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oligomers produced during secondary surface nucleation induce the permeabilization of cell membranes through to their lipophilic properties. Associated with these events, higher basal levels of cytosolic Ca 2+ , increased Ca 2+ influx upon stimulation, and delayed recovery of Ca 2+ levels in neurons are then observed since the early phases, leading to multiple Ca 2+ homeostasis alterations that persist with disease progression [ 18 ].…”
Section: Alpha-synuclein Structure and Physiological Functionmentioning
confidence: 99%
“…of cell membranes through to their lipophilic properties. Associated with these events, higher basal levels of cytosolic Ca 2+ , increased Ca 2+ influx upon stimulation, and delayed recovery of Ca 2+ levels in neurons are then observed since the early phases, leading to multiple Ca 2+ homeostasis alterations that persist with disease progression [18]. Native α-syn is present in synaptic terminals, in the nucleus of neuronal cells [19], mitochondria [20], endoplasmic reticulum (ER) [21], Golgi apparatus (GA) [22], and in the endolysosomal system [23].…”
Section: Rem Behavior Disorder (Rbd)mentioning
confidence: 99%
“…Conversely, LRRK2 G2019S mutant neurons had faster calcium oscillations which aligned with the hyperexcitable phenotype (increased network burst frequency) observed on MEA activity. One possible mechanism underlying this observation is that high expression of α-Syn has been shown to disrupt calcium homeostasis and potentially alter neuronal activity 50 . This is supported by our observation of increased α-Syn accumulation in all mutant PD disease lines.…”
Section: Discussionmentioning
confidence: 99%
“…Almost nothing is known about the electrophysiological activities and Ca 2+ homeostatic processes in the emerging mDA neurons, most likely playing a role already during the earliest stages of mDA neuron development and long before they have established a proper connectivity with their efferent and afferent targets, although their mitochondrial energy metabolism and autophagic/lysosomal clearance of misfolded proteins and defective organelles are now beginning to be unraveled in the human context in vitro ( section 3.1.2 ). This fact has probably led to a collective neglect of these aspects arguing that they might not be biologically relevant, although several evidences have meanwhile accumulated suggesting the opposite is true for the developing mammalian VM and mDA neurons, both in the wildtype and in the PD context ( Chan et al, 2007 ; Rockhill et al, 2009 ; Ferrari et al, 2012 ; Ramirez-Latorre, 2012 ; Kim et al, 2020 ; Carola et al, 2021 ; Akrioti et al, 2022 ; Stern et al, 2022 ; Virdi et al, 2022 ). It has been suggested that such ion- and neurotransmitter-driven early (immature) activities in developing neurons represent “phenotypic checkpoints” integrating intrinsic TF-mediated (genetic) developmental pathways with extrinsic signals from the surrounding environment to ensure the overall correct establishment of a neuron’s identity and function in the broader context of the nervous system ( Ben-Ari and Spitzer, 2010 ).…”
Section: Discussionmentioning
confidence: 99%